If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = (x + -1)(x + -1)(x + -2i)(x + 2i) Multiply f * x fx = (x + -1)(x + -1)(x + -2i)(x + 2i) Reorder the terms: fx = (-1 + x)(x + -1)(x + -2i)(x + 2i) Reorder the terms: fx = (-1 + x)(-1 + x)(x + -2i)(x + 2i) Reorder the terms: fx = (-1 + x)(-1 + x)(-2i + x)(x + 2i) Reorder the terms: fx = (-1 + x)(-1 + x)(-2i + x)(2i + x) Multiply (-1 + x) * (-1 + x) fx = (-1(-1 + x) + x(-1 + x))(-2i + x)(2i + x) fx = ((-1 * -1 + x * -1) + x(-1 + x))(-2i + x)(2i + x) fx = ((1 + -1x) + x(-1 + x))(-2i + x)(2i + x) fx = (1 + -1x + (-1 * x + x * x))(-2i + x)(2i + x) fx = (1 + -1x + (-1x + x2))(-2i + x)(2i + x) Combine like terms: -1x + -1x = -2x fx = (1 + -2x + x2)(-2i + x)(2i + x) Multiply (1 + -2x + x2) * (-2i + x) fx = (1(-2i + x) + -2x * (-2i + x) + x2(-2i + x))(2i + x) fx = ((-2i * 1 + x * 1) + -2x * (-2i + x) + x2(-2i + x))(2i + x) fx = ((-2i + 1x) + -2x * (-2i + x) + x2(-2i + x))(2i + x) fx = (-2i + 1x + (-2i * -2x + x * -2x) + x2(-2i + x))(2i + x) fx = (-2i + 1x + (4ix + -2x2) + x2(-2i + x))(2i + x) fx = (-2i + 1x + 4ix + -2x2 + (-2i * x2 + x * x2))(2i + x) fx = (-2i + 1x + 4ix + -2x2 + (-2ix2 + x3))(2i + x) Reorder the terms: fx = (-2i + 4ix + -2ix2 + 1x + -2x2 + x3)(2i + x) fx = (-2i + 4ix + -2ix2 + 1x + -2x2 + x3)(2i + x) Multiply (-2i + 4ix + -2ix2 + 1x + -2x2 + x3) * (2i + x) fx = (-2i * (2i + x) + 4ix * (2i + x) + -2ix2 * (2i + x) + 1x * (2i + x) + -2x2 * (2i + x) + x3(2i + x)) fx = ((2i * -2i + x * -2i) + 4ix * (2i + x) + -2ix2 * (2i + x) + 1x * (2i + x) + -2x2 * (2i + x) + x3(2i + x)) Reorder the terms: fx = ((-2ix + -4i2) + 4ix * (2i + x) + -2ix2 * (2i + x) + 1x * (2i + x) + -2x2 * (2i + x) + x3(2i + x)) fx = ((-2ix + -4i2) + 4ix * (2i + x) + -2ix2 * (2i + x) + 1x * (2i + x) + -2x2 * (2i + x) + x3(2i + x)) fx = (-2ix + -4i2 + (2i * 4ix + x * 4ix) + -2ix2 * (2i + x) + 1x * (2i + x) + -2x2 * (2i + x) + x3(2i + x)) Reorder the terms: fx = (-2ix + -4i2 + (4ix2 + 8i2x) + -2ix2 * (2i + x) + 1x * (2i + x) + -2x2 * (2i + x) + x3(2i + x)) fx = (-2ix + -4i2 + (4ix2 + 8i2x) + -2ix2 * (2i + x) + 1x * (2i + x) + -2x2 * (2i + x) + x3(2i + x)) fx = (-2ix + -4i2 + 4ix2 + 8i2x + (2i * -2ix2 + x * -2ix2) + 1x * (2i + x) + -2x2 * (2i + x) + x3(2i + x)) Reorder the terms: fx = (-2ix + -4i2 + 4ix2 + 8i2x + (-2ix3 + -4i2x2) + 1x * (2i + x) + -2x2 * (2i + x) + x3(2i + x)) fx = (-2ix + -4i2 + 4ix2 + 8i2x + (-2ix3 + -4i2x2) + 1x * (2i + x) + -2x2 * (2i + x) + x3(2i + x)) fx = (-2ix + -4i2 + 4ix2 + 8i2x + -2ix3 + -4i2x2 + (2i * 1x + x * 1x) + -2x2 * (2i + x) + x3(2i + x)) fx = (-2ix + -4i2 + 4ix2 + 8i2x + -2ix3 + -4i2x2 + (2ix + 1x2) + -2x2 * (2i + x) + x3(2i + x)) fx = (-2ix + -4i2 + 4ix2 + 8i2x + -2ix3 + -4i2x2 + 2ix + 1x2 + (2i * -2x2 + x * -2x2) + x3(2i + x)) fx = (-2ix + -4i2 + 4ix2 + 8i2x + -2ix3 + -4i2x2 + 2ix + 1x2 + (-4ix2 + -2x3) + x3(2i + x)) fx = (-2ix + -4i2 + 4ix2 + 8i2x + -2ix3 + -4i2x2 + 2ix + 1x2 + -4ix2 + -2x3 + (2i * x3 + x * x3)) fx = (-2ix + -4i2 + 4ix2 + 8i2x + -2ix3 + -4i2x2 + 2ix + 1x2 + -4ix2 + -2x3 + (2ix3 + x4)) Reorder the terms: fx = (-2ix + 2ix + 4ix2 + -4ix2 + -2ix3 + 2ix3 + -4i2 + 8i2x + -4i2x2 + 1x2 + -2x3 + x4) Combine like terms: -2ix + 2ix = 0 fx = (0 + 4ix2 + -4ix2 + -2ix3 + 2ix3 + -4i2 + 8i2x + -4i2x2 + 1x2 + -2x3 + x4) fx = (4ix2 + -4ix2 + -2ix3 + 2ix3 + -4i2 + 8i2x + -4i2x2 + 1x2 + -2x3 + x4) Combine like terms: 4ix2 + -4ix2 = 0 fx = (0 + -2ix3 + 2ix3 + -4i2 + 8i2x + -4i2x2 + 1x2 + -2x3 + x4) fx = (-2ix3 + 2ix3 + -4i2 + 8i2x + -4i2x2 + 1x2 + -2x3 + x4) Combine like terms: -2ix3 + 2ix3 = 0 fx = (0 + -4i2 + 8i2x + -4i2x2 + 1x2 + -2x3 + x4) fx = (-4i2 + 8i2x + -4i2x2 + 1x2 + -2x3 + x4) Solving fx = -4i2 + 8i2x + -4i2x2 + 1x2 + -2x3 + x4 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -4i2x-1 + 8i2 + -4i2x + x + -2x2 + x3 Simplifying f = -4i2x-1 + 8i2 + -4i2x + x + -2x2 + x3 Reorder the terms: f = 8i2 + -4i2x-1 + -4i2x + x + -2x2 + x3
| 3x^2+4y^2=48 | | 40=-16t^2 | | 4x+8=15x-3+64 | | 3r+4-7=1 | | 3x-41=x+93 | | (F/2)-7=-1 | | 40=-16t^2+c | | Y=-3x^2+81+9 | | 0=29x+x^2-525 | | 5s^2-36=32 | | 6x/x-2 | | 0-q=4 | | 2y-6y=8 | | 9-b=10 | | (x-1)(3x-2)=0 | | 80pi=2r+r | | -2+8+5x=35 | | X+2X+4X+6X+6X=78 | | 30.865=1.44*ln(x)+35.053 | | 1*x=0.01 | | y=1.44*ln(x)+35.053 | | 2/5y=30 | | 7q-14q=2 | | (V/4)-3=5 | | X+21=3x+7 | | 6r-8=1.5r-6 | | 100000=x+.6x | | 5^-2-x=1/125 | | 10x-76=6x-20 | | x/2(2/2-6/2) | | 3x-4-5x=1x+4+1x | | -(2)0= |